2009
DOI: 10.1007/s10637-009-9235-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmented antitumor effects of combination therapy of cisplatin with ethaselen as a novel thioredoxin reductase inhibitor on human A549 cell in vivo

Abstract: Ethaselen (1, 2-[bis (1, 2-Benzisoselenazolone-3 (2H) -ketone)] ethane, BBSKE), as a novel organoselenium compound targeting thioredoxin reductase (TrxR), has been reported to inhibit tumor growth and TrxR activity in several human tumor cell lines. It has now entered Phase I clinical trails. Here we report the effects of ethaselen and cisplatin (cis-diamminedichloroplatinum II, DDP) combination therapy (ethaselen 36 mg/kg, i.g., o.d. x 10 d and cisplatin 1 mg/kg, i.p., single at day 0) on human A549-grafted n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Our lab has previously reported the significant growth inhibition, apoptosis induction and cell cycle retarding effect of BBSKE against A549, MCF-7, PANC-1, and RKO cells in vitro (Shi et al, 2003;Zhao et al, 2006). BBSKE treatment in combination with cisplatin, fluorouracil or radiation therapy showed synergistic effect and attenuated toxicity in LoVo, BGC-823, and A549 cells (Li et al, 2008;Tan et al, 2010;Fu et al, 2011;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…Our lab has previously reported the significant growth inhibition, apoptosis induction and cell cycle retarding effect of BBSKE against A549, MCF-7, PANC-1, and RKO cells in vitro (Shi et al, 2003;Zhao et al, 2006). BBSKE treatment in combination with cisplatin, fluorouracil or radiation therapy showed synergistic effect and attenuated toxicity in LoVo, BGC-823, and A549 cells (Li et al, 2008;Tan et al, 2010;Fu et al, 2011;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, a synergistic effect has been observed in the study of the combination of Ethaselen and cisplatin (CDDP) in vivo. Studies have shown that the antitumor efficacy of cisplatin on the stomach cancer cell line BGC-823, the human lung cancer cell line PG-BE1, the subcutaneous transplanted lung cancer cell line A459 in the nude mice, and the human colon adenocarcinoma cell line LoVo would be further enhanced through synergetic combination with Ethaselen (Tan et al, 2010). These previous studies have indicated that there is a close link of the antitumor mechanism between Ethaselen and CDDP, suggesting that Ethaselen may be a potential and efficient method for reversing cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In light of above reports, using ebselen as a lead compound, ethaselen [1,2-(bis-1,2-benzisoselenazol-3(2H)-one)ethane, Fig. 1], as a typical thioredoxin reductase (TrxR) inhibitor, has been synthesized and found to exhibit broad spectrum of antitumor effects with slight toxicity (He et al, 2012;Tan et al, 2010;Xing et al, 2008;Zhao et al, 2006). Currently, a Phase I clinical trail of ethaselen for antitumor activity is being carried out in China (He et al, 2012).…”
Section: Introductionmentioning
confidence: 99%